Ruta graveolens and rutin, as its major compound: investigating their effect on spatial memory and passive avoidance memory in rats - Shirin Asgharian; Mohammad Reza Hojjati; Mohsen Ahrari; Elham Bijad; Fatemeh Deris; Zahra Lorigooini (Taylor & Francis Group, 2020)
Context There are numerous pharmacological activities for Ruta graveolens and its bioactive constituent, rutin, on learning and memory. Objective This study aimed to examine the effect of R. graveolens and rutin on memory in rats. Materials and methods In this study animals were treated with the hydroalcholic extract of R. graveolens and rutin by IP injection for 10 days. Behavioural and biochemical tests as well as HPLC analysis and antioxidant activity of extract have been evaluated. Results R. graveolens extract and rutin significantly increased learning and improved spatial memory, as well as secondary latency; moreover, there were significant increases in the serum and brain antioxidant capacity as well as the level of TBARS in serum and brain tissues. Results also showed that R. graveolens has significant DPPH radical scavenging effect (IC50: 159.17 ± 1.56 μg/mL). The HPLC analysis of extract showed that caffeic acid (19.92 ± 0.01), rutin (40.15 ± 0.01), and apigenin (0.84 ± 0.01) mg/g of dry extract are the main components of the extract. Discussion and conclusion Regarding the effects of R. graveolens extract and rutin on animal brain cells, memory function, and learning, additional studies, including clinical trials, might be beneficial in producing natural supplementary drugs from this herb.